Insights on Using WALC Platform as a Learning Tool - Le, C.P.; Soares, F.; Costas, S. (International Journal of Engineering Pedagogy (iJEP), 2012)
<!–[if gte mso 9]> 800x600 <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false DE X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Normale Tabelle"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; –> <!–[endif] –> WALC (Web Assisted Laboratory for Control engineering on-line education) platform was developed by a multidisciplinary team of university researchers. WALC is a configurable platform on Automation, Process Control and Numerical Methods subjects, enabling the on-line access to virtual and remote laboratories. Special emphasis was given to remotely access the platform, making WALC an educational tool. It is well known that students have different levels of motivation and different attitudes towards teaching and learning. Configurable learning environments play, then, a relevant role. Following this trend, using advances in technology, WALC is a platform in fast adaptation to new study methods. In order to understand the students´ response, questionnaire results were analyzed and discussed.